2012
DOI: 10.5090/kjtcs.2012.45.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Follow-up after Cryopreserved Homograft Replacement in the Aortic Position

Abstract: BackgroundThe long-term results of homografts used in systemic circulation are controversial. We assessed the long-term results of using a cryopreserved homograft for an aortic root or aorta and its branch replacement.Materials and MethodsFrom June 1995 to January 2010, 23 patients (male:female=15:8, 45.4±15.6 years) underwent a homograft replacement in the aortic position. The surgical techniques used were aortic root replacement in 15 patients and aortic graft interposition in 8 patients. Indications for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Park et al [ 4 ] used homografts for aortic root replacement in 15 patients and for aortic graft interposition in 8. These results were compatible with ours, but use of the homograft was different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al [ 4 ] used homografts for aortic root replacement in 15 patients and for aortic graft interposition in 8. These results were compatible with ours, but use of the homograft was different.…”
Section: Discussionmentioning
confidence: 99%
“…The 30-day mortality rate was 9.1% (n=3) in our patients. Park et al [ 4 ] reported an early mortality rate of 8.7%. The 10-year overall survival rate in our patients was 63.4%±9.5%, and was 59.6% for Park et al [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 4 mm from the short edge of the rectangular section, a 4-0 non-absorbable monofilament suture Premilene ® , (Karck and Haverich, 2005;Park et al, 2012) was inserted and tied to form a loop.…”
Section: Biomechanical Performance Ii: Materials Properties (Uniaxial mentioning
confidence: 99%